THE EFFECT OF BITTER MELON (Momordica charantia) EXTRACT ON SUPEROXIDE DISMUTASE LEVELS AND IMMUNOHISTOCHEMICAL PROFILE IN THE LIVER OF DIABETIC RATS - Nurul Wahdania; I Nyoman Suarsana; I Made Kardena (Fakultas Kedokteran Hewan Universitas Udayana, 2026)
Chronic hyperglycemia in diabetes can trigger oxidative stress and reduce the activity of superoxide dismutase (SOD) as an endogenous antioxidant. Bitter melon (Momordica charantia) has bioactive compounds that have the potential to support the antioxidant system. This study aims to determine the effect of bitter melon extract on the levels and immunohistochemical profile of SOD in the liver tissue of diabetic rats. A total of 20 male rats were divided into four groups: normal controls, diabetic controls, and two diabetic groups given bitter melon extract at doses of 50 mg/kg BW and 100 mg/kg BW for 21 days. SOD levels were measured using the ELISA method, while the SOD profile was analyzed through immunohistochemical staining. The results showed that diabetes reduced SOD levels in the liver tissue of rats compared to the normal control group, with values ​​of 3,873 ± 0,298 ng/mL and 1,916 ± 0,220 ng/mL, respectively. Administration of bitter melon fruit extract increased SOD levels, with a higher response at a dose of 100 mg/kg BW (3,089 ± 0,202 ng/mL), compared to 50 mg/kg BW (2,884 ± 0,272 ng/mL). Immunohistochemical analysis showed a stronger intensity of SOD staining expression in liver tissue after administration of the extract, especially at a dose of 100 mg/kg BW. Further research is needed to evaluate other antioxidant enzymes and determine varying doses to enhance the endogenous antioxidant system.